Intensification of biochemical purification of oil wastewater process by acting on biocenosis activity - Semenova, Olena; Bublienko, Natalia; Smirnova, Elizabeth; Shylofost, Tatiana; Pastushenko, A. (My University, 2012)
Questions intensification of biochemical sewage treatment using yeast autolysate. Studied the stimulatory effect of yeast autolysate on the kinetics of the purification process and the quality of sludge from the viewpoint of its utilization. Розглянуто питання інтенсифікації біохімічного очищення стічних вод за допомогою дріжджового автолізату. Вивчено стимулюючий вплив дріжджового автолізату на кінетику процесу очищення і на якість активного мулу з точки зору можливості його утилізації.
Keywords: стічні води; дріжджовий автолізат; активний мул; біохімічне очищення; waste water; yeast autolysate; activated sludge; biochemical purification; кафедра екології та екоменеджменту; кафедра іноземних мов професійного спрямування